TERT c.3150 G > C (p.K1050N): a founder Ashkenazi Jewish variant associated with telomere biology disorders - Kelvin César de Andrade; Emilia M. Pinto; Tianna Zhao; Logan P. Zeigler; Jung Kim; Neelam Giri; Jeremy S. Haley; Lisa J. McReynolds; Oscar Florez-Vargas; Aaron H. Phillips; Richard W. Kriwacki; Sherifa A. Akinniyi; et al. (npj Genomic Medicine)
Abstract Pathogenic germline variants in telomerase (TERT) cause telomere biology disorders (TBDs) and are associated with bone marrow failure, pulmonary fibrosis, and other complications. TERT c.3150 G > C (p.K1050N) is frequent in the Ashkenazi Jewish (ASH) population and has been identified in ASH families with TBDs. Whole-genome sequencing of 96 p.K1050N heterozygotes from the UK Biobank and All of Us databases revealed a shared haplotype block, supporting a founder effect. Analyses of 15 additional p.K1050N cases validated this haplotype and identified mitochondrial and Y-STR haplogroups consistent with ASH ancestry. Clinical assessments showed that p.K1050N contributes to TBD phenotypes and shortened telomeres, while population data suggest incomplete penetrance. p.K1050N reduces telomerase activity and processivity, and decreases PCNA expression and BrdU incorporation, impairing cell proliferation. Our findings establish TERT p.K1050N as an ASH founder variant associated with TBDs, underscoring the need for genetic screening and long-term clinical studies.